Criminalizing the Armchair Terrorist: Entrapment and the Domestic Terrorism Prosecution - Gantar, Dejan M. (2014)
A variety of factors plague a defendant's rights in a domestic terrorism trial. This Note focuses on contemporary domestic terrorism prosecutions in which the defendants raise an entrapment defense. It suggests that federal courts apply a lower standard for prosecutors in proving predisposition by allowing nothing more than evidence of a defendant's religious or political beliefs, or general impulse to lash out, to demonstrate predisposition. This Note further argues that this evidentiary laxity establishes a double standard in terrorism cases, and also manifests First Amendment problems. The crux of this Note is that federal courts should refine the entrapment doctrine within the terrorism-prosecution context. Rather than modify the doctrine-which arguably would result in convictions contrary to established precedent-federal courts should treat terrorism-related offenses like any other traditional crime. Further, the courts should exercise their inherent power to dismiss charges on due process grounds when the government's conduct in investigations is outrageous enough to violate fundamental notions of fairness under the Due Process Clause. By doing the above, federal courts would better preserve the constitutional rights of criminal defendants, as well as distinguish between legitimate and illegitimate threats of terrorism